Atkinson and Stiglitz theorem with endogenous human capital accumulation - Hisahiro Naito (Osaka University, Institute of Social and Economic Research (ISER), 2003)
Recently, several papers have re-examined the so called production efficiency theorem and the Atkinson and Stiglitz theorem on commodity taxes in the optimal taxation literature. Naito (1998) showed that indirect redistribution through production distortion or consumption distortion can Pareto-improve welfare and that the two theorems do not necessarily hold when different factors are imperfect substitutes and factor prices are endogenous. On the other hand, Saez (2001) argued that in the long run where human capital accumulation is endogenous, the two theorems are still valid. This paper points out that the result of Saez (2003) depends on the assumption on the dimension of the type of human capital. This paper shows that if different people have different comparative advantage in accumulating different types of human capital, the Atkinson and Stiglitz theorem does not hold.
Keywords: H21; H23; 330; human capital accumulation; non-linear income taxation and comparative advantage; Optimale Verteilung; Optimale Besteuerung; Verbrauchsteuer; Bildungsinvestition; Theorie